Exercise, appetite and appetite-regulating hormones: Implications for food intake and weight control - Stensel, D. (Annals of Nutrition and Metabolism, 2010)
Knowledge about the relationship between exercise and appetite is important both for athletes wishing to optimise performance and for those interested in maintaining a healthy body weight. A variety of hormones are involved in appetite regulation including both episodic hormones, which are responsive to episodes of feeding, and tonic hormones, which are important regulators of energy storage over the longer term (e.g. insulin and leptin). Notable among the episodic appetite-regulating hormones is ghrelin, which plays a unique role in stimulating appetite and energy intake. Many studies have demonstrated that acute bouts of moderately vigorous exercise transiently suppress appetite and this has been termed `exercise-induced anorexia`. The mechanisms by which acute exercise suppresses appetite are not fully understood but may involve lowered concentrations of ghrelin and increased concentrations of satiety hormones, notably peptide YY and glucagon-like peptide 1. Evidence suggests that chronic exercise training typically causes a partial but incomplete compensation in energy intake perhaps due to beneficial changes in appetite-regulating hormones. The lack of a full compensatory response of appetite to exercise may facilitate the development of a negative energy balance and weight loss although there is individual variability in the response to exercise. From a practical standpoint athletes should not feel concerned that exercise will cause overeating as there is limited evidence to support this. For those desiring weight loss there may be some merit in performing exercise in the postprandial period as a means of enhancing the satiating effect of a meal but additional evidence is required to confirm the effectiveness of this strategy.